EVALUASI PELAPORAN KONTRAK GADAI SYARIAH PERSPEKTIF FATWA DSN-MUI - Yenny Susilawati (LP2M IAI Miftahul Ulum Pamekasan, 2017)
In every contract of the concept of sharia must meet the principle of legal compliance with the concept of Islam, that's how things happen in the Islamic pawn contract. This contract, the reporting must be in accordance with the reporting standards in the DSN-MUI Fatwa. This research uses the type of qualitative research with literature method. This study found that the reporting of pawning contracts is in accordance with sharia through several contracts namely; qard contract, rahn contract, and ijarah contract are in accordance with DSN-MUI Fatwa or in accordance with sharia principles, namely there is a qard contract as a pure loan agreement to the customer, rahn contract as a contract agreed upon by the customer as the surrender of collateral for safekeeping by the pawnshop with followed by the next contract which is the ijarah contract as a contract that complements the pawn contract and alternative pawnshop to obtain a term which is calculated based on collateral contract.